2014
DOI: 10.1038/mt.2013.273
|View full text |Cite
|
Sign up to set email alerts
|

Oral Delivery of Bioencapsulated Proteins Across Blood–Brain and Blood–Retinal Barriers

Abstract: Delivering neurotherapeutics to target brain-associated diseases is a major challenge. Therefore, we investigated oral delivery of green fluorescence protein (GFP) or myelin basic protein (MBP) fused with the transmucosal carrier cholera toxin B subunit (CTB), expressed in chloroplasts (bioencapsulated within plant cells) to the brain and retinae of triple transgenic Alzheimer's disease (3×TgAD) mice, across the blood-brain barriers (BBB) and blood-retinal barriers (BRB). Human neuroblastoma cells internalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 49 publications
(57 reference statements)
1
87
0
Order By: Relevance
“…15,45,46 In addition, elimination of highly expensive purification, cold storage, transportation, and sterile injections significantly reduces their costs. Although we have not optimized the codons for FVIII expression in the current investigation, it has been reported that protein expression can reach up to 70% of the total leaf protein under optimal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…15,45,46 In addition, elimination of highly expensive purification, cold storage, transportation, and sterile injections significantly reduces their costs. Although we have not optimized the codons for FVIII expression in the current investigation, it has been reported that protein expression can reach up to 70% of the total leaf protein under optimal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…8,45 Antigen-CTB-GM1 complexes then traffic retrograde through the Trans-Golgi network into the lumen of the endoplasmic reticulum. 35,[46][47][48] Because of the furin cleavage site, proteolytic cleavage occurs in the Trans-Golgi network, so that FIX antigen can be exocytosed and released into extracellular fluid, whereas CTB is retained intracellularly. 8,35,46 The orally delivered FIX is identical in amino acid sequence to the mature recombinant FIX used for systemic delivery, but lacks glycosylation and g-carboxylation (and therefore does not have coagulation activity and cannot restore hemostasis).…”
Section: Discussionmentioning
confidence: 99%
“…CNTB fusion proteins expressed in chloroplasts form pentameric structures that are highly resistant to detergents, and this hampers solubilization due to tight interactions between CNTB monomers, mediated by 30 hydrogen bonds, seven salt bridges, and hydrophobic interactions (Miyata et al, 2012). In our previous studies (Boyhan and Daniell, 2011;Kwon et al, 2013;Kohli et al, 2014;Shil et al, 2014), multimeric forms exist even after treatment with DTT, detergents (SDS), and boiling. Also, acid (pH 2) could not completely dissociate CNTB pentamers due to the reformation of multimeric structures.…”
Section: New Solution For the Quantitation Of Insoluble Multimeric Prmentioning
confidence: 99%
“…A wide range of proteins, from very small antimicrobial peptides (Lee et al, 2011) or hormones (Boyhan and Daniell, 2011;Kwon et al, 2013) to very large proteins encoded by bacterial, viral, fungal, animal, and human genes, have been expressed successfully in plant chloroplasts (DeGray et al, 2001;Daniell et al, 2009;Verma et al, 2010;Shenoy et al, 2014;Sherman et al, 2014;Shil et al, 2014). Most importantly, expressed proteins are highly stable when lyophilized plant cells are stored at ambient temperature (Kwon et al, 2013;Lakshmi et al, 2013;Kohli et al, 2014;Jin and Daniell, 2015). Therefore, oral delivery of proinsulin or exendin-4 reduced blood sugar levels similar to injected proteins (Boyhan and Daniell, 2011;Kwon et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation